Die Apologetiek van C. S. Lewis: ’n Gereformeerd-Teologiese besinning - Deel 2 - Brand, G. v W. (Verbum et ecclesia, 1996)
The apologetics of C. S. Lewis: a Reformed theological reflection - Part 2 In this, the second part of a two part study, in which the validity of C. S. Lewis’s apologetics is evaluated from a Reformed perspective, the author explains the apologetic approach of C. S. Lewis, by examining his writings on the topic, in order to demonstrate the legitimacy of Lewis’s approach in terms of prerequisites delineated in the first part of the study.